Genetic and Imaging Approaches Reveal Pro-Inflammatory and Immunoregulatory Roles of Mast Cells in Contact Hypersensitivity - Gaudenzio, Nicolas; Marichal, Thomas; Galli, Stephen J.; Reber, Laurent L. (Frontiers in Immunology, 2018)
Contact hypersensitivity (CHS) is a common T cell-mediated skin disease induced by epicutaneous sensitization to haptens. Mast cells (MCs) are widely deployed in the skin and can be activated during CHS responses to secrete diverse products, including some with pro-inflammatory and anti-inflammatory functions. Conflicting results have been obtained regarding pathogenic versus protective roles of MCs in CHS, and this has been attributed in part to the limitations of certain models for studying MC functions in vivo. This review discusses recent advances in the development and analysis of mouse models to investigate the roles of MCs and MC-associated products in vivo. Notably, fluorescent avidin-based two-photon imaging approaches enable in vivo selective labeling and simultaneous tracking of MC secretory granules (e.g., during MC degranulation) and MC gene activation by real-time longitudinal intravital microscopy in living mice. The combination of such genetic and imaging tools has shed new light on the controversial role played by MCs in mouse models of CHS. On the one hand, they can amplify CHS responses of mild severity while, on the other hand, can limit the inflammation and tissue injury associated with more severe or chronic models, in part by representing an initial source of the anti-inflammatory cytokine IL-10.